Doxorubicin-induced Chronic Heart Failure is Alleviated by Gentiopicroside by Inhibiting Oxidative Stress and Inflammation - Guo, Yujun; Gao, Pan; Deng, Wei; Wang, Shujun (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim/Background: To study the Oxidative stress and inflammation inhibited by Gentiopicroside in chronic heart failure induced by doxorubicin. Materials and Methods: The procured healthy rats were first divided into four groups group I was maintained as healthy control and the others were subjected to the induction of doxorubicin-induced chronic heart failure (Dox-CHF) by2.5 mg/kg/day DOX by i.p. on alternate days for 2 weeks. Then the Dox-CHF rats were further divided into three groups, group II was used as the Dox-CHF control rats, the group III and group IV were administered with Gentiopicroside (25 mg/kg b.wt and 50 mg/kg b.wt, respectively) for 2 weeks. The heart tissue and body weight, Serum Lipids, Lipid Peroxidation and Antioxidants, Biomarkers enzymes for Cardiac Injury such as Aspartate Aminotransferase (AST), Creatine Kinase (CK), and Lactate Dehydrogenase (LDH)), Immunological Biomarkers such as Heart-type fatty acid-binding protein H-FABP, Glycogen Phosphorylase isoenzyme BB (GP-BB), and Creatine Kinase-MB isoenzyme (CK-MB), Inflammatory Interferon-γ (INF-γ), and Monocyte Chemotactic Protein-1 (MCP-1)) and pro-inflammatory (TNF-α and IL-6) levels were estimated at week 0 and week 2. Results: The cardioprotective properties of Gentiopicroside were evaluated in a Doxorubicin-induced cardiomyopathy model. Gentiopicroside was highly effective in combating the cardiotoxic attributes manifested by DOX at 2.5 mg/kgs, such as abnormal hemodynamic parameters, oxidative stress, and inflammation. Based on the reduced cardiotoxicity biomarkers, it was capable of reducing serum lipids, enhancing host antioxidant expression, and suppressing lipid peroxidation. According to the results of this study, Gentiopicroside reduces oxidative stress and inhibits inflammatory responses in DOX-administered individuals, suppressing cardiotoxicity. Conclusion: All the test results concluded that Gentiopicroside can treat DOX-induced cardiotoxicity.
Keywords: Gentiopicroside; Doxorubicin; Cardiotoxicity; Oxidative stress; Anti-inflammatory